2021
DOI: 10.1002/lno.11777
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Prochlorococcus temperature niches in the lab and across ocean basins

Abstract: Niche theory suggests that the realized niche occupied by an organism in the field is a subset of the fundamental niche space of the organism, absent additional biotic and abiotic factors. Though often assumed, this discrepancy is rarely tested for specific organisms, and could act as a source of error in model predictions of biogeographical shifts resulting from temperature change which assume niche theory constraints. Here, we quantify the difference between fundamental and realized temperature niches for fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 83 publications
2
12
0
Order By: Relevance
“…The species in our model did, however, have realized niche optima that were, on average, slightly colder than the fundamental temperature niche optimums (𝛿 T opt < 0; Figure 9b). Previous studies (Kingsolver et al, 2013;Smith et al, 2021) have observed this pattern across a range of organisms. Fundamental temperature niches are typically, and in this model, assumed to have a left-or negativelyskewed curve where growth above the optimum temperature decreases rapidly compared to growth below the optimum, as measured from laboratory experiments where growth is calculated from incubations at constant temperatures (Anderson et al, 2021;Norberg, 2004;Thomas et al, 2012).…”
Section: Temporal Storage Effectssupporting
confidence: 62%
See 3 more Smart Citations
“…The species in our model did, however, have realized niche optima that were, on average, slightly colder than the fundamental temperature niche optimums (𝛿 T opt < 0; Figure 9b). Previous studies (Kingsolver et al, 2013;Smith et al, 2021) have observed this pattern across a range of organisms. Fundamental temperature niches are typically, and in this model, assumed to have a left-or negativelyskewed curve where growth above the optimum temperature decreases rapidly compared to growth below the optimum, as measured from laboratory experiments where growth is calculated from incubations at constant temperatures (Anderson et al, 2021;Norberg, 2004;Thomas et al, 2012).…”
Section: Temporal Storage Effectssupporting
confidence: 62%
“…Phytoplankton growth for each species in each box (here we drop the j subscript) is a function of temperature (Thomas et al., 2012):ÎŒi)(Tgoodbreak=aebT][1goodbreak−T−ziw22$$ {\mu}_i(T)=a{e}^{bT}\left[1-{\left(\frac{T-{z}_i}{\frac{w}{2}}\right)}^2\right] $$where the constants a and b are empirically derived values that control the exponential increase of growth rate with temperature and the trait parameters ( z i and w ) control the species‐specific response to temperature. The values for a , the growth rate at 0°C (0.81 day −1 ), and b , the exponential increase in growth rate with temperature (0.0631 day −1 ), are taken from empirical analyses (Bissinger et al., 2008) and are commonly utilized (Smith et al., 2021; Thomas et al., 2012). All model species have the same niche width ( w ; 10°C), which is roughly the niche width of observed North Atlantic phytoplankton species (Irwin et al., 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth rates and metabolic fluxes were adjusted for temperature effects by comparing in situ growth temperatures to a model of temperature-dependent growth, parameterized for each strain. Our approach provides a strain-specific parameterization while avoiding the effects of adaptive laboratory evolution, which can be substantial (55). First, the Arrhenius activation energy E a was calculated on the basis of growth rates determined in batch cultures of 12 Prochlorococcus strains (9,56).…”
Section: Temperature Dependence Of Metabolic Ratesmentioning
confidence: 99%